Effect of plant‐based diets on obesity‐related inflammatory profiles: a systematic review and meta‐analysis of intervention trials. (13th July 2016) - Eichelmann, F.; Schwingshackl, L.; Fedirko, V.; Aleksandrova, K.
Summary: Plant‐based dietary interventions have been proposed to reduce obesity induced chronic low‐grade inflammation and hence prevent chronic disease risk; however, human evidence remains unclear. This systematic review and meta‐analysis of intervention trials aimed to assess the effect of plant‐based diets on obesity‐related inflammatory biomarker profiles. Medline, EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for articles published until January 2016 and mean differences in biomarkers of inflammatory status were assessed for: C‐reactive protein (CRP), interleukin‐6 (IL‐6), tumour necrosis factor‐alpha (TNF‐ɑ), soluble intercellular adhesion molecule 1 (sICAM), leptin, adiponectin and resistin. Of initially identified 2, 583 publications, 29 met the meta‐analysis inclusion criteria [a total of 2, 689 participants]. Consumption of plant‐based diets was associated with a reduction in the mean concentrations of the following biomarkers: CRP [effect size, −0.55 mg/l, 95% confidence intervals (CI): −0.78; −0.32, I 2  = 94.4%], IL‐6 [effect size, −0.25 ng/l, 95% CI: −0.56; 0.06, I 2  = 74%], and, to some degree, sICAM (−25.07 ng/ml [95% CI: −52.32; 2.17, I 2  = 93.2%]). No substantial effects were revealed for TNF‐ɑ, resistin, adiponectin and leptin. Plant‐based diets are associated with an improvement in obesity‐related inflammatory profiles and could provide means for therapy and prevention of chronic disease risk.